Enhancing Early Childhood Creativity Through Loose Parts Play Activities Based on Islamic Values - S Septriany; A. Ahmadi (Golden Ratio of Data in Summary, 2026)
This study aims to improve early childhood creativity through loose parts play activities based on Islamic values at KB Wijaya Kusuma Pacitan. The research used a quantitative approach with a pre-experimental one-group pretest-posttest design involving 10 children. Data were collected through observation using a creativity assessment sheet covering fluency, flexibility, originality, and elaboration. The results showed a significant increase from a pretest mean of 6.8 to a posttest mean of 12.9. The paired sample t-test result (0.000 < 0.05) indicated a significant effect. Thus, loose parts play based on Islamic values is effective in enhancing early childhood creativity holistically.